Syndecan-4 levels in bronchoalveolar lavage fluid and serum in non-small cell lung cancer - Abdul Azis, Asrul; Santoso, Arif; Djaharuddin, Irawaty; Iskandar, Harun; Ilyas, Muhammad; Lihawa, Nurjannah (Medical Journal of Indonesia, 2024)
BACKGROUND Lung cancer has the highest cancer-related mortality rate worldwide. Research has been conducted to improve early detection and markers of predictive value but only focused on the expression of syndecan-4 (SDC4) in serum. Studies in bronchoalveolar lavage (BAL) fluids of non-small cell lung cancer (NSCLC) patients are still limited. This study aimed to evaluate the clinical value of SDC4 in serum and BAL in NSCLC patients. METHODS Blood serum and BAL fluids were obtained from 44 patients with NSCLC and 41 non-cancer patients as the control. The level of SDC4 was measured. The relationships between SDC4 and clinicopathologic factors were also analyzed. RESULTS Serum SDC4 levels in NSCLC patients were significantly lower than the control group (p = 0.002). Furthermore, the disease stages and serum SDC4 levels had a negative correlation, which was lower in the advanced stage (IIIb/IV) than in the initial stage (I/II/IIIa) (p = 0.517). The same results were obtained from BAL fluids SDC4 levels, which were significantly lower in the advanced stage (IIIb/IV) than in the early stage (I/II/IIIa) (p = 0.007). CONCLUSIONS Serum SDC4 levels in NSCLC patients were lower than those of non-cancer patients. They also performed different results in disease stages. SDC4 could be a helpful biomarker in NSCLC.